Nitraria retusa fruit prevents penconazole-induced kidney injury in adult rats through modulation of oxidative stress and histopathological changes - Mariem Chaâbane; Mohamed Koubaa; Nejla Soudani; Awatef Elwej; Malek Grati; Kamel Jamoussi; Tahia Boudawara; Semia Ellouze Chaabouni; Najiba Zeghal (Taylor & Francis Group, 2017)
Context: Nitraria retusa (Forssk.) Asch. (Nitrariaceae) is a medicinal plant which produces edible fruits whose antioxidant activity has been demonstrated. Objective: The current study elucidates the potential protective effect of N. retusa fruit aqueous extract against nephrotoxicity induced by penconazole, a triazole fungicide, in the kidney of adult rats. Materials and methods: Adult Wistar rats were exposed either to penconazole (67 mg/kg body weight), or to N. retusa extract (300 mg/kg body weight) or to their combination. Penconazole was administered by intra-peritoneal injection every 2 days from day 7 until day 15, the sacrifice day, while N. retusa extract was administered daily by gavage during 15 days. Oxidative stress parameters, kidney biomarkers and histopathological examination were determined. Results: Nitraria retusa extract administration to penconazole treated rats decreased kidney levels of malondialdehyde (−10%), hydrogen peroxide (−12%), protein carbonyls (PCOs, −11%) and advanced oxidation protein products (AOPP, −16%); antioxidant enzyme activities: catalase (−13%), superoxide dismutase (−8%) and glutathione peroxidase (GPx, −14%), and the levels of non-enzymatic antioxidants: non-protein thiols (−9%), glutathione (−7%) and metallothionein (−12%). Furthermore, this plant extract prevented kidney biomarker changes by reducing plasma levels of creatinine, urea, uric acid and LDH and increasing those of ALP and GGT. Histopathological alterations induced by penconazole (glomeruli fragmentation, Bowman's space enlargement, tubular epithelial cells necrosis and infiltration of inflammatory leucocytes) were attenuated following N. retusa administration. Discussion and conclusion: Our results indicated that N. retusa fruit extract had protective effects against penconazole-induced kidney injury, which could be attributed to its phenolic compounds.